Mapping current trends and hotspots in myasthenia gravis from 2003 to 2022: a bibliometric analysis - Tian, Yukun; Shen, Qiqi; Peng, Siyang; Meng, Linghao; Fang, Ruiying; Xiong, Anni; Li, Shaohong; Yang, Yajing; Chang, Weiqian; Ni, Jinxia; Zhu, Wenzeng (Frontiers in Neurology, 2023)
Introduction Research on myasthenia gravis (MG) has undergone rapid development in recent years. This article aimed to elucidate the characteristics of MG publications over the past 20 years and analyze emerging trends using bibliometric methods. Methods Information on MG articles was obtained from the Web of Science Core Collection and stored in Excel for quantitative analyses. Bibliometric analyses were performed using CiteSpace and VOSviewer to visualize publications according to countries/regions, institutions, journals, and authors. Results A total of 3,610 publications were included in the analysis. The USA had the highest number of publications (NP) and H-index. Among the institutions, the University of Oxford had the highest NP, followed by the University of Toronto and Duke University. Close cooperation was observed among countries and institutions. The most productive author was Renato Mantegazza, followed by Jan J. Verschuuren, and Amelia Evoli. Muscle & Nerve published the most articles on MG, followed by the Journal of Neuroimmunology and Neuromuscular Disorders. The keyword with the highest strength is “neuromuscular transmission,” followed by “safety” and “rituximab.” Co-citation analysis includes 103 publications cited at least 65 times, categorized into four clusters. Additionally, 123 keywords cited more than 40 times were analyzed and divided into five clusters. Conclusion This bibliometric analysis shows the framework of research over the past 20 years by mapping the scholarly contributions of various countries or regions, institutions, journals, and authors in MG. The analysis also explores future trends and prospective directions, emphasizing individualized treatment based on subtypes, novel immunotherapeutic approaches, and thymectomy.